Son Devir Çağatay Edebiyatının İki Önemli Kadın Şairi : Nadire ve Üveysi - Tolkun, Selahittin (Kitabevi, 2001)
The two women poets, Nâdire and Üveysî lived and produced written work during the first half of the 18th century. Which was a time of regression and collapse in Chagatay Literature. Both were known at the time and have left a mark even after their death.
Two Important Women Poets in the Last Era of Chagatay Literature : Nadire and Üveysi
Keywords: Chagatay Literature; Women Poet; Kokand Rulership; Nâdire; Üveysî